The Moderator Role of Attitude For Technology in the Connection Between Attitude for the Teaching Profession and Professional Resilience - Merve,; Darıca, Nilüfer; Ugras, Mustafa (My University, 2024)
Attitude for the teaching profession has an important place in the professional resilience of teacher candidates. Examining the moderating role of pre-service teacher (PST) attitudes for technology will contribute to the enrichment of the literature by looking at the relationship between their attitudes for the profession and their professional resilience from a different perspective. The aim of this study is to examine the moderating role of PST' attitudes for technology in the relationship between their attitudes for the profession and their professional resilience. Relational survey model was used in the study. The research group consists of 407 PST in Gaziantep, which can be reached with an easy sample. As data collection tools; 'Personal Information Form', 'Attitude Scale For the Teaching Profession', 'Professional Resilience Scale for Teaching Candidates', 'Attitude Scale For Technology' were used. The scales used were filled in with a paper-pencil form by the PST. The data gathered throughout the investigation were assessed utilizing quantitative analysis techniques with the use of SPSS software. Descriptive statistics, Pearson correlation analysis, and Hayes (Process) analysis 1 were employed in the examination of the data. The model is used. As a result of the research, it was seen that the attitudes of PST for the profession predicted their professional resilience. However, the relationship between these PST' attitudes for the profession and their professional resilience differs according to their attitudes for technology. It has been determined that PST' attitudes for the profession and their attitudes for technology have a moderating role in the relationship between their professional resilience.
Keywords: Attitude for the teaching profession; professional resilience; attitude for technology